1996
DOI: 10.1074/jbc.271.50.32375
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the Transforming Growth Factor-β2 Gene Is Dependent on an E-box Located between an Essential cAMP Response Element/Activating Transcription Factor Motif and the TATA Box of the Gene

Abstract: Transforming growth factor-␤2 (TGF-␤2) is an important regulator of cell proliferation and differentiation; however, its transcriptional regulation is not well understood. Here we report characterization of an essential E-box motif, positioned at ؊50/؊45 between a previously described functional cAMP response element/ activating transcription factor site and the TATA box of the human TGF-␤2 promoter. By site-directed mutagenesis, we demonstrate that this E-box motif is necessary for the promoter activity, not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…TGF-␤2 promoter/CAT chimeric gene constructs and their mutants (see Fig. 1) were described previously (16,(23)(24)(25). Unless otherwise noted, the null vector, pUC-19 (Invitrogen, Carlsbad, CA) was used to keep the total DNA concentration the same in each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…TGF-␤2 promoter/CAT chimeric gene constructs and their mutants (see Fig. 1) were described previously (16,(23)(24)(25). Unless otherwise noted, the null vector, pUC-19 (Invitrogen, Carlsbad, CA) was used to keep the total DNA concentration the same in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in electrophoretic gel mobility shift assays, ATF-1 and cAMP-responsive element binding protein (CREB) bind to the CRE/ATF motif, and the upstream stimulatory factors 1 and 2 (USF1 and -2) bind to the E-box element (26 -28). Previous studies have demonstrated that these transcription factors are present in nuclear extracts prepared from both F9 EC cells and F9-differentiated cells and can bind to their respective cis-regulatory elements in vitro (25,27,28). Expression of a dominant-negative USF expression plasmid reduces the expression of a TGF-␤2 promoter/reporter construct by approximately 80% (25).…”
mentioning
confidence: 99%
See 3 more Smart Citations